GE_GERICHTE C/31026/2010 vom 10. Mai 2012 - GE Cour de justice (2012)
EXPERTISE; PREUVE; RESPONSABILITÉ DE DROIT PRIVÉ; CONTRAT DE TRAVAIL | aLPC.196 / CC.8 / CPC.316.3 / CO.53 / CO.321.e / CO.42.2 / CO.44.1